Caracteristicile sistemului CDI în România - Stănculescu, Manuela Sofia; Stănescu, Simona; Stoica, Laura (Calitatea Vieții, 2007)
This paper presents the conclusions of the study conducted by RIQL, regarding the existing situation in the field of research, development and inovation, in Romania. The study focused on: i) the evaluation of the financing and organisation of the research field in Romania; ii) existing problems and opportunities and iii) possible solutions and proposals for improvement of the existing situation, made by managers and employees from public and private research institutions (research institutes, universities and companies).